PENGABDIAN KKN-MANDIRI DESA GOLO WUAS KABUPATEN MANGGARAI TIMUR - Daniel Wolo; Yulius Saprianus Dala Ngapa; Marıa LS Harıyanti (LPPM Universitas Flores, 2020)
The Independent Real Work Lecture (KKN) program has been implemented in Golo Wuas Village, Elar Selatan District, East Manggarai Regency. The purpose of implementing the program is that lecturers and students gain learning experiences through direct involvement with the community by finding, formulating, solving, and overcoming problems in the field. The method of implementing KKN activities is carried out in the form of data collection, socialization, and training involving the government and the community directly. Some of the results achieved from this Independent Community Service Program are some of the activities that have been carried out (a) Assistance in teaching and learning activities in mathematics subjects to SDK Ndawang students, (b) Counseling and parquetry of making husk charcoal fertilizer and organic fertilizer, (c) empowerment seminars community in the health sector